The Coherence and Cohesion Level of the Descriptive Texts in SMA English Textbook “Look Ahead an English Course X” Published by Erlangga - Jumatriadi Jumatriadi (PALAPA, 2013)
Textbook is one of the material references of the English teaching at school. It is used to run English learning process. A book plays an important role in modern life. It functions to get information and knowledge. A teacher cannot deliver any instructional objectives to the students without using media in teaching and learning process. So, textbook is the main source of instructional materials. Based on the result of investigation that researcher has done, all of the writing texts especially descriptive texts in “Look Ahead an English Course X” were coherent, because the level of coherence in that text was in good and fair level, and the highest percentage level of coherence was 80%. The texts that have been analyzed from the textbook “Look Ahead An English Course X” were in good textbook because the highest total of percentage level of coherence was in good and fair level because a paragraph will be coherent or good if the type of thematic progression is constant in one type and inconstant or change from one type to others type of each paragraph, and most of thematic progression was used in the descriptive texts.